PENGGUNAAN ALIH KODE DAN CAMPUR KODE DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X SMA NEGERI 6 KOTA TERNATE - Rafik M. Abasa (Cakrawala Bahasa, 2021)
This research was conducted with the aim to determine the use of code switching and code mixing, also to find out the factors causing code switching and code mixing in Indonesian language learning in class X SMA Negeri 6 Ternate City. The method used in this study is a Qualitative Descriptive Method. The data source was Indonesian language teacher and class X students of SMA Negeri 6 Ternate City, which only consisted of a portion of 20 students. The research data is the use of code switching and code mixing of class X students of the 6th eerily of Ternate City. Based on data analysis, it was concluded that the data collection technique used was direct observation of a problem located in SMA Negeri 6 Ternate City. This study aimed to obtain additional data. This interview was conducted to reveal the effectiveness of the use of code switching and code mixing in Indonesian language learning. Records conducted by researchers to obtain data from the research objectives. Occurrence of the use of code switching and code mixing in Indonesian language learning for class X students of SMA Negeri 6 Ternate City, namely the use of code switching and code mixing is the switching of formal language codes, informal language code switching, and the occurrence of code switching between languages while the code mix is mixed code of words, phrases, clauses. Factors causing code switching and code mixing in Indonesian language learning in class X SMA Negeri 6 Ternate City are the occurrence of code switching due to speakers or speakers, listeners or interlocutors, Changes in the situation due to the presence of a third person, Changes in the situation from formal to informal or conversely, Change of Speaker Topic while mixed code because of the background of the attitudes of speakers and linguists.